Visions of sainthood in medieval Rome : the lives of Margherita Colonna - Colonna, Giovanni, 1298?-1343 or 1344.; Stefania; Field, Larry F.; Knox, Lezlie S.; Field, Sean L. (Sean Linscott), 1970- (Notre Dame : University of Notre Dame Press, 2017)
In Visions of Sainthood in Medieval Rome, Larry F. Field, Lezlie S. Knox, and Sean L. Field present the first English translations of Margherita Colonna's two ""lives"" and a dossier of associated texts, along with thoroughly researched contextualization and scholarly examination.
The Life of the Blessed Virgin Margherita of the Family Name Colonna / by Giovanni Colonna -- Three Papal Bulls on the Foundation of San Silvestro in Capite in 1285 -- A New Statement on Margherita Colonna's Perfection of the Virtues / by Stefania -- Three Later Papal Bulls Concerning Boniface VIII, the Colonna, and San Silvestro in Capite -- Mariano of Florence's Account of Margherita Colonna's Translation -- Appendix: Rome, Bibliotheca Casanatense Ms. 104 -- Select Bibliography -- Index.
Includes bibliographical references and index.
Description based on print version record.
JSTOR
Keywords: Colonna, Margherita, -- 1255-1280.; Christian biography -- Italy; Biographies chrétiennes -- Italie; Christian biography; Italy